Effects of indium exposure on respiratory symptoms: a retrospective cohort study in Japanese workers using health checkup data - Mitsuhashi,Toshiharu (PeerJ, 2020)
Background Indium compounds are known health hazards for lung cancer and interstitial pneumonia. Furthermore, they are related to emphysema, alveolar proteinosis, and cholesterol granuloma. In Japan, laws were revised in 2013 to tighten regulations on indium exposure in workplaces. However, its impact on the health of workers who handle indium has not been evaluated. This study aimed to investigate whether subjective respiratory symptoms in these workers have reduced after the 2013 amendment in the regulations. Methods The subjects were workers from certain areas of Japan who had undergone health checkups between January 1, 2013, and June 30, 2015. Indium-handling and non-handling workers were categorized into the exposed and less-exposed groups, respectively. Based on the findings of health checkups during this period, the hazard ratio of subjective respiratory symptoms (cough, sputum production, shortness of breath, and palpitation) and its 95% confidence intervals (CIs) were calculated with the less-exposed group as the reference. The Prentice-Williams-Peterson model was used for calculation, and a model that adjusted for coarse analysis and potential confounding factors was adopted. Results Overall, 2,561 workers (from 22 companies) who underwent 6,033 health checkups were included. The total person-years were 2,562.8 years, and 162 outcome events occurred. The hazard ratios of the exposed group were 1.65 (95% CI [1.14–2.39]: p = 0.008) and 1.61 (95% CI [1.04–2.50]: p = 0.032) in the crude and adjusted models, respectively. Conclusion Indium-handling workers had a high hazard of the subjective respiratory symptoms than non-indium -handling workers despite stricter regulations on indium exposure in workplaces. This indicates the need for further changes to the legislation to protect the health of workers exposed to harmful substances in workplaces. Further studies including larger diverse cohorts are needed to validate our findings.
Keywords: Cohort study; Indium; Public health; Workplace; Occupational health; Respiratory symptoms; Survival analysis